Cytotoxic properties, glycolytic effects and high-resolution respirometry mitochondrial activities of Eriocephalus racemosus against MDA-MB 231 triple-negative breast cancer - Francis Adu-Amankwaah; Candice Februarie; Kudakwashe Nyambo; Gerald Maarman; Ndivhuwo Tshililo; Lawrence Mabasa; Vuyo Mavumengwana; Lucinda Baatjies (BMC Complementary Medicine and Therapies)
Abstract Introduction Triple-negative breast cancer (TNBC) represents a significant global health crisis due to its resistance to conventional therapies and lack of specific molecular targets. This study explored the potential of Eriocephalus racemosus (E. racemosus) as an alternative treatment for TNBC. The cytotoxic properties and high-resolution respirometry mitochondrial activities of E. racemosus against the MDA-MB 231 TNBC cell line were evaluated. Methods Hexane solvent and bioactive fraction extractions of E. racemosus were performed, while mass spectrometry-based metabolite profiling was used to identify the phytochemical constituents of the extracts. The extracts were further tested against MDA-MB 231 TNBC cells to determine their cytotoxicity. The mode of cell death was determined using flow cytometry. The activities of caspases 3, 8, and 9 were assessed using a multiplex activity assay kit. Glycolytic activity and High-resolution respirometry measurements of mitochondrial function in the MDA-MB 231 cell line were conducted using the Seahorse XFp and Oroboros O2K. Results Metabolite profiling of E. racemosus plant crude extracts identified the presence of coumarins, flavonoids, sesquiterpenoids, triterpenoids, and unknown compounds. The extracts demonstrated promising cytotoxic activities, with a half maximal inhibitory concentration (IC50) of 12.84 µg/mL for the crude hexane extract and 15.49 µg/mL for the bioactive fraction. Further, the crude hexane and bioactive fraction extracts induced apoptosis in the MDA-MB-231 TNBC cells, like the reference drug cisplatin (17.44%, 17.26% and 20.25%, respectively) compared to untreated cells. Caspase 3 activities confirmed the induction of apoptosis in both cisplatin and the plant crude extracts, while caspase 8 and 9 activities confirmed the activation of both the intrinsic and extrinsic apoptosis pathways. Increased levels of glycolytic activity were observed in the hexane crude extract. High-resolution respiratory measurements showed elevated mitochondrial activities in all mitochondrial states except for complex-IV activity. Conclusion These findings support further exploration of E. racemosus as a potential therapeutic agent for TNBC, offering a promising avenue for the development of targeted treatments with minimal adverse effects.